2013
DOI: 10.5171/2013.813339
|View full text |Cite
|
Sign up to set email alerts
|

A Visual Dot-Probe Task as a Measurement of Attentional Bias and its Relationship with the Symptoms of Posttraumatic Stress Disorder among Women with Breast Cancer

Abstract: Self-reported measurements of attentional bias are possibly influenced by social desirability, conscious awareness, or introspection. This study developed a visual dot-probe task to study the relationship between attentional bias and posttraumatic stress disorder among women with breast cancer. Fifty six women with breast cancer were presented with a series of face pairs, which were equally divided into positive-neutral and negative-neutral pairs. One face pair was shown for each trial, which consisted of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Two studies tested if attentional bias was associated with poor psychological adjustment to breast cancer. Using a dot‐probe task, negative attentional bias toward sad faces was associated with greater symptoms of post‐traumatic stress disorder in Chinese women with breast cancer . Another dot probe–based study assessed attentional bias toward cancer‐related words and reported that women with breast cancer showed attentional bias toward cancer‐related words, but not social threat–related words .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies tested if attentional bias was associated with poor psychological adjustment to breast cancer. Using a dot‐probe task, negative attentional bias toward sad faces was associated with greater symptoms of post‐traumatic stress disorder in Chinese women with breast cancer . Another dot probe–based study assessed attentional bias toward cancer‐related words and reported that women with breast cancer showed attentional bias toward cancer‐related words, but not social threat–related words .…”
Section: Introductionmentioning
confidence: 99%
“…14 To date,4 studies have adopted experimental paradigms to study attentional bias in cancer adjustment with mixed results. Two studies 15,16 tested if attentional bias was associated with poor psychological adjustment to breast cancer. Using a dot-probe task, negative attentional bias toward sad faces was associated with greater symptoms of posttraumatic stress disorder in Chinese women with breast cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The visual dot-probe paradigm (MacLeod, Mathews, & Tata, 1986) adopted in the present study was based on studies by Brosan, Hoppitt, Shelfer, Sillence, and Mackintosh (2011) and Chan, Ho, Law, and Pau (2013). The visual dot-probe task was conducted in a well-lit, quiet laboratory room with no external distractions.…”
Section: The Experiments Apparatus and Stimulusmentioning
confidence: 99%
“…Each trial was run in the following sequence. First, a black fixation cross (4 pixels wide, subtending 0.62 9 0.62 degree) was displayed in the centre of the screen for 1,000 ms. Second, a picture pair consisting of a neutral picture and an emotional (positive or negative) picture located approximately 13 cm apart (measured from their centres) was displayed in the top and bottom halves of the screen, respectively, for 500 ms based on the study of Bradley, Mogg, and Lee (1997) and a previous study conducted among Chinese breast cancer patients (Chan et al, 2013). Each picture was unframed and subtended 14.8 (W) 9 11.1 (H) degrees.…”
Section: The Experiments Apparatus and Stimulusmentioning
confidence: 99%